Anti-aging overhead insulated wire and preparation method thereof
By using specific materials in overhead insulated wires to form the insulation layer and outer sheath, and by optimizing the ratio and modification, the aging problem of the wires in harsh environments is solved, achieving significant improvement in aging resistance.
Patent Information
- Application Number
- CN202510694010.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-08-05
AI Technical Summary
Existing overhead insulated wires are prone to aging in harsh environments, resulting in cracks and falls off of the insulation layer, and their aging resistance is limited.
Perfluoroether rubber, mica powder, fatty acid esters, 2,2-bis-(4-hydroxyphenyl)hexafluoropropane and other materials are used to form the insulating layer, and the outer sheath is formed using cross-linked polyethylene, nanobarium sulfate and other materials to form the outer sheath. The dispersion and aging resistance of the material are improved by optimizing raw material ratio and modification treatment.
The aging resistance of overhead insulated wires is significantly improved, and the tensile strength change rate after aging is reduced to -1.14%, effectively resisting environmental factors such as ultraviolet rays, temperature changes and humidity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wires and cables, and more specifically, to an aging-resistant overhead insulated conductor and a preparation method thereof. Background Art
[0002] Overhead insulated conductors are used for power transmission and distribution, typically in overhead power lines. Unlike bare conductors, overhead insulated conductors are covered with a layer of insulating material, generally referred to as insulation. Traditional overhead insulated conductors are subject to long-term exposure to harsh environments such as ultraviolet light, high temperatures, and humidity, causing the insulation layer to age easily. This aging process is prone to cracking and partial shedding. Therefore, developing an aging-resistant overhead insulated conductor is crucial for its long-term safe operation.
[0003] In the related art, mica powder is added to the insulation layer of overhead insulated conductors to improve the aging resistance of overhead insulated conductors, but the improvement effect is weak. Therefore, the development of an overhead insulated conductor with excellent aging resistance is crucial to the current development of overhead insulated conductors. Summary of the Invention
[0004] In order to improve the aging resistance of overhead insulated conductors, the present application provides an aging-resistant overhead insulated conductor and a preparation method thereof.
[0005] In a first aspect, the present application provides an aging-resistant overhead insulated conductor, which adopts the following technical solution: An aging-resistant overhead insulated conductor comprises a conductor, an insulating layer and an outer sheath; the conductor is an aluminum conductor; the insulating layer comprises the following raw materials in parts by weight: 50-70 parts of perfluoroether rubber, 1-5 parts of mica powder, 0.1-0.5 parts of fatty acid ester, 0.5-1 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2-3 parts of antioxidant, and 6-10 parts of ultraviolet absorber; the outer sheath comprises the following raw materials in parts by weight: 80-100 parts of cross-linked polyethylene, 10-20 parts of nano-barium sulfate, 1-3 parts of plasticizer, 5-10 parts of flame retardant, 0.5-1 parts of antioxidant, 1-2 parts of ultraviolet absorber, and 0.5-1 parts of light stabilizer.
[0006] The insulation layer of the aging-resistant overhead insulated conductor of the present application is composed of 50-70 parts of perfluoroether rubber, 1-5 parts of mica powder, 0.1-0.5 parts of fatty acid ester, 0.5-1 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2-3 parts of antioxidant, and 6-10 parts of ultraviolet absorber. Any value within the respective ranges can be selected, and the aging resistance of the overhead insulated conductor can be improved. In addition, the outer sheath of the aging-resistant overhead insulated conductor of the present application is composed of 80-100 parts of cross-linked polyethylene, 10-20 parts of nano-barium sulfate, 1-3 parts of plasticizer, 5-10 parts of flame retardant, 0.5-1 parts of antioxidant, 1-2 parts of ultraviolet absorber, and 0.5-1 parts of light stabilizer. Any value within the respective ranges can be selected, and the aging resistance of the overhead insulated conductor can be improved.
[0007] By adopting the above technical solution, perfluoroether rubber (PFER) is selected, which has higher aging resistance than fluororubber and can better ensure the excellent aging resistance of overhead insulated conductors. The addition of mica powder can increase the complexity of the internal space of the insulation layer, thereby improving the aging resistance of the overhead insulated conductor. The addition of fatty acid ester can reduce the agglomeration of mica powder, thereby improving the dispersion of mica powder in the insulation material, thereby improving the aging resistance of the overhead insulated conductor. The addition of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane can increase the crosslink density, thereby enhancing the aging resistance of the overhead insulated conductor.
[0008] Using cross-linked polyethylene (XLPE) as the primary material for the outer sheath prevents cracking or powdering even under long-term exposure to sunlight. It also offers excellent temperature resistance, reaching -40-90°C, and prevents moisture from penetrating the insulation layer. It exhibits excellent UV and oxidation resistance, effectively resisting environmental factors such as UV radiation, temperature fluctuations, humidity, and rain, resulting in high aging resistance for the overhead insulated conductors. Nano-barium sulfate, a functional filler, enhances the outer sheath's resistance to corrosive media such as acid rain, industrial waste gas, and salt spray. The addition of nano-barium sulfate reduces the penetration rate of solvent molecules, thereby improving the aging resistance of the overhead insulated conductors. Furthermore, the smooth surface of nano-barium sulfate reduces melt viscosity, increasing the fluidity of the XLPE and improving the dispersion of the remaining raw materials within the XLPE.
[0009] Preferably: an aging-resistant overhead insulated conductor, the insulating layer comprises the following raw materials in parts by weight: 55-65 parts of perfluoroether rubber, 1.5-2.5 parts of mica powder, 0.2-0.4 parts of fatty acid ester, 0.7-0.9 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2.4-2.8 parts of antioxidant, and 7-9 parts of ultraviolet absorber; the outer sheath comprises the following raw materials in parts by weight: 85-95 parts of cross-linked polyethylene, 14-18 parts of nano-barium sulfate, 1.5-2.5 parts of plasticizer, 7-9 parts of flame retardant, 0.7-0.9 parts of antioxidant, 1.4-1.8 parts of ultraviolet absorber, and 0.7-0.9 parts of light stabilizer.
[0010] The insulation layer of the aging-resistant overhead insulated conductor of the present application may be made of 55-65 parts of perfluoroether rubber, 1.5-2.5 parts of mica powder, 0.2-0.4 parts of fatty acid ester, 0.7-0.9 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2.4-2.8 parts of antioxidant, and 7-9 parts of ultraviolet absorber. Any value within the respective ranges may be selected, and the aging resistance of the overhead insulated conductor can be improved. In addition, the outer sheath of the aging-resistant overhead insulated conductor of the present application is made of 85-95 parts of cross-linked polyethylene, 14-18 parts of nano-barium sulfate, 1.5-2.5 parts of plasticizer, 7-9 parts of flame retardant, 0.7-0.9 parts of antioxidant, 1.4-1.8 parts of ultraviolet absorber, and 0.7-0.9 parts of light stabilizer. Any value within the respective ranges may be selected, and the aging resistance of the overhead insulated conductor can be improved.
[0011] Preferably, the weight ratio of the fatty acid ester to the mica powder is 1:(23-27).
[0012] By adopting the above technical solution and adjusting the weight ratio of fatty acid ester to mica powder, the dispersibility of mica powder in the insulation layer raw material can be further improved, thereby improving the aging resistance of the overhead insulated conductor.
[0013] Preferably, the nano-barium sulfate is prepared by modification, specifically by mixing a titanate coupling agent and liquid paraffin in a volume ratio of 1:(1-2), adding dried nano-barium sulfate, and stirring at 80-120°C for 30-60 minutes at a stirring rate of 1000-3000 r / min. Finally, the nano-barium sulfate is crushed to 50-200 nm to obtain the modified nano-barium sulfate.
[0014] By adopting the above technical solution, the titanate coupling agent is uniformly coated on the surface of the nano-barium sulfate to improve the dispersion of the nano-barium sulfate in the outer sheath raw material, and the coating temperature is controlled to avoid slow reaction due to too low temperature and decomposition of the titanate coupling agent due to too high temperature. After coating, the nano-barium sulfate is crushed to 50-200nm, which can further reduce the agglomeration of the modified nano-barium sulfate, thereby achieving high activation and high dispersion of the nano-barium sulfate, and ultimately improving the aging resistance of the overhead insulated conductor.
[0015] Preferably, the weight ratio of the titanate coupling agent to nano-barium sulfate is 1:(100-200).
[0016] By adopting the above technical solution and adjusting the weight ratio of titanate coupling agent and nano-barium sulfate, the dispersibility of nano-barium sulfate in the outer sheath raw material can be further improved, thereby further improving the aging resistance of the overhead insulated wire.
[0017] Preferably, the outer sheath further comprises the following raw materials in parts by weight: 5-10 parts of nano zinc oxide and 0.05-0.5 parts of polyethylene wax.
[0018] By adopting this technical solution, the added nano-zinc oxide has a high shielding effect against ultraviolet rays, reducing internal photodegradation of the outer sheath material and the rate of oxidation, while also improving the outer sheath's wear resistance and crack propagation resistance. Polyethylene wax improves the dispersion of nano-zinc oxide in the outer sheath material, creating a synergistic effect with the nano-zinc oxide.
[0019] Preferably, the weight ratio of the polyethylene wax to nano zinc oxide is 1:(20-80).
[0020] By adopting the above technical solution and controlling the weight ratio of polyethylene wax and nano zinc oxide, the dispersibility of nano zinc oxide in the outer sheath raw material can be further improved, thereby further improving the aging resistance of the overhead insulated wire.
[0021] In a second aspect, the present application provides a method for preparing any of the above-mentioned aging-resistant overhead insulated conductors.
[0022] A method for preparing an aging-resistant overhead insulated conductor comprises the following steps: mixing, extruding, and vulcanizing various raw materials for an insulating layer to obtain an insulating layer material; mixing, extruding, and vulcanizing various raw materials for an outer sheath to obtain an outer sheath material; extruding and coating the insulating layer material on the surface of the conductor, and then extruding and coating the outer sheath on the surface of the insulating layer to obtain an aging-resistant overhead insulated conductor.
[0023] In summary, this application includes at least one of the following beneficial technical effects: (1) This application controls the types and dosages of various raw materials in the aging-resistant overhead insulated conductors, so that the rate of change in tensile strength of the overhead insulated conductors after aging is -2.87% to -2.65%, thereby improving the aging resistance of the overhead insulated conductors.
[0024] (2) This application modifies nano-barium sulfate and adjusts the weight ratio of nano-barium sulfate and titanate coupling agent so that the change rate of tensile strength of overhead insulated conductors after aging is -2.45% to -2.30%, thereby improving the aging resistance of overhead insulated conductors.
[0025] (3) This application further improves the aging resistance of the overhead insulated conductor by adding nano zinc oxide and polyethylene wax to the outer sheath raw material and controlling the dosage thereof, so that the change rate of the tensile strength of the overhead insulated conductor after aging is -1.20% to -1.14%. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to specific embodiments.
[0027] The following raw materials in this application are all commercially available products. They are provided for the purpose of fully disclosing the raw materials in this application and should not be construed as limiting the sources of the raw materials. Specifically, they are: aluminum wire, model LG-70; perfluoroether rubber, model DF-260; mica powder, particle size 400 mesh; fatty acid ester, using pentaerythritol ester, model PETS; 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, active substance content 98%; antioxidant, model Antioxidant 1010; UV absorber, model UV-329; cross-linked polyethylene, model LDPE 681I; nano-barium sulfate, particle size 50nm; flame retardant, using melamine phosphate; plasticizer, model DOP; light stabilizer, model UV-292; titanate coupling agent, model TC-201; liquid paraffin, model TC / 300#; nano-zinc oxide, particle size 50nm; polyethylene wax, model LP0020P.
[0028] The following is an example of the preparation of modified ultrafine mica powder Preparation Example 1 The modified nano-barium sulfate of Preparation Example 1 was prepared by the following steps: 90 kg of nano-barium sulfate was dried at 110° C. for 3 h, and then cooled to obtain dried nano-barium sulfate; 1 kg of titanate coupling agent was mixed with 1 kg of liquid paraffin, and dried nano-barium sulfate was added and stirred at 100° C. for 45 minutes at a stirring rate of 2000 r / min. Finally, the mixture was crushed to 100 nm to obtain modified nano-barium sulfate.
[0029] Preparation Example 2-5 The preparation methods of the modified nano-barium sulfate in Preparation Examples 2-5 are the same as those in Preparation Example 1, except that the amounts of nano-barium sulfate used are 100 kg, 150 kg, 200 kg, and 210 kg, respectively, and the types and amounts of other raw materials are the same as those in Preparation Example 1. Example
[0030] The aging-resistant overhead insulated conductor of Example 1 is prepared by the following preparation method: According to the dosage in Table 1, the raw materials of the insulation layer were mixed at 120°C for 15 minutes, extruded (the temperature of the first zone was 150°C, the temperature of the second zone was 170°C, and the temperature of the third zone was 160°C), and vulcanized at 140°C for 10 minutes to obtain the outer sheath material; According to the dosage in Table 2, the raw materials of the outer sheath were mixed at 120°C for 15 minutes, extruded (the temperature of the first zone was 150°C, the temperature of the second zone was 170°C, and the temperature of the third zone was 160°C), and vulcanized at 140°C for 10 minutes to obtain the outer sheath material; The insulating layer material is extruded and coated on the surface of the conductor, and then the outer sheath is extruded and coated on the surface of the insulating layer to obtain an aging-resistant overhead insulated conductor.
[0031] Examples 2-5 The preparation methods of the aging-resistant overhead insulated conductors of Examples 2-5 are the same as those of Example 1, except that the dosages of the raw materials for the insulating layer are different, as shown in Table 1 for details.
[0032] Table 1 Amount of each raw material added in the insulation layer of Examples 1-5 (kg)
[0033] Table 2 Amount of each raw material in the outer sheath of Examples 1-5 (kg)
[0034] Examples 6-10 The preparation method of the aging-resistant overhead insulated wires of Examples 6-10 is the same as that of Example 3, except that the nano-barium sulfate in the raw material of the aging-resistant overhead insulated wires is the modified nano-barium sulfate prepared in Preparation Examples 1-5, and the types and dosages of the other raw materials are the same as those in Example 3. Example
[0035] The preparation method of the aging-resistant overhead insulated conductor of Example 11 is the same as that of Example 8, except that it further comprises 8 kg of nano zinc oxide and 0.44 kg of polyethylene wax, and the types and amounts of other raw materials are the same as those of Example 8.
[0036] Examples 12-15 The preparation methods of the aging-resistant overhead insulated conductors of Examples 12-15 are the same as those of Example 11, except that the dosage of polyethylene wax is 0.4 kg, 0.16 kg, 0.1 kg, and 0.08 kg, respectively. The types and dosages of other raw materials are the same as those of Example 11.
[0037] Comparative Example 1 The preparation method of the aging-resistant overhead insulated wire of Comparative Example 1 is the same as that of Example 1, except that an equal amount of mica powder in the insulating layer is replaced by carbon black, and the types and dosages of other raw materials are the same as those of Example 1.
[0038] Comparative Example 2 The preparation method of the aging-resistant overhead insulated wire of Comparative Example 2 is the same as that of Example 1, except that no fatty acid ester is added to the raw materials of the insulating layer, and the types and dosages of the other raw materials are the same as those of Example 1.
[0039] Comparative Example 3 The preparation method of the aging-resistant overhead insulated wire of Comparative Example 3 is the same as that of Example 1, except that an equal amount of nano-barium sulfate in the outer sheath raw material is replaced by nano-silicon dioxide, and the types and dosages of other raw materials are the same as those of Example 1.
[0040] Performance testing The performance of the overhead insulated wires obtained in different Examples 1-15 and Comparative Examples 1-3 was tested, and the test results are shown in Table 3.
[0041] Aging resistance: Aging resistance tests were conducted in accordance with GB / T 3512-2014 "Rubber vulcanized or thermoplastic rubber - Hot air accelerated aging and heat resistance tests". The tensile strength of each specimen after aging was tested according to the above-mentioned tensile strength test method, and the rate of change of tensile strength after aging was calculated. During the aging resistance test, a cabinet-type hot air aging chamber in method A was used, with air changes of 5 times per hour, a temperature of 200°C, and a time of 72 hours. The tensile strength was measured in accordance with GB / T 528-2009 "Rubber vulcanized or thermoplastic rubber - Determination of tensile stress-strain properties". The specimen was a type A ring specimen. See Table 3 for details.
[0042] Table 3 Performance test results of different overhead insulated conductors
[0043] The test results in Table 3 show that the tensile strength change rate of the overhead insulated wire obtained in the present application after aging is as low as -1.14%, which significantly improves the aging resistance of the overhead insulated cable.
[0044] Combined with the performance test data of the overhead insulated conductors of Examples 1-5, it can be seen that the change rate of the tensile strength of the overhead insulated conductors of Examples 2-4 after aging is -2.87% to -2.65%, which are all higher than those of Example 1 and Example 5, indicating that when the weight ratio of fatty acid ester to mica powder in the raw materials of the insulating layer of the overhead insulated conductor is 1: (23-27), it is more appropriate, which improves the aging resistance of the overhead insulated conductor.
[0045] Combined with the performance test data of the overhead insulated conductors in Examples 6-10, it can be seen that the change rate of the tensile strength of the overhead insulated conductors in Examples 7-9 after aging is -2.45% to -2.30%, which is higher than that in Example 6 and Example 10, indicating that when modifying the nano-barium sulfate, a weight ratio of titanate coupling agent to nano-barium sulfate of 1: (100-200) is more appropriate, which improves the aging resistance of the overhead insulated conductors.
[0046] Combined with the performance test data of the overhead insulated conductors of Examples 11-15, it can be seen that the tensile strength change rate of the overhead insulated conductors of Examples 12-14 after aging is -1.20% to -1.14%, which are all higher than those of Example 11 and Example 15, indicating that the weight ratio of polyethylene wax to nano zinc oxide is 1: (20-80) which is more appropriate, thereby improving the aging resistance of the overhead insulated conductors.
[0047] In addition, based on the performance test data of the aging-resistant overhead insulated wires in comparative examples 1-3 and Example 1, it was found that adding mica powder and fatty acid esters to the raw materials of the insulating layer of the aging-resistant overhead insulated wires and adding nano-barium sulfate to the raw materials of the outer sheath can improve the aging resistance of the overhead insulated wires to varying degrees.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. An aging-resistant overhead insulated conductor, characterized in that: The invention comprises a conductor, an insulating layer and an outer sheath; the conductor is an aluminum wire; the insulating layer comprises the following raw materials in parts by weight: 50-70 parts of perfluoroether rubber, 1-5 parts of mica powder, 0.1-0.5 parts of fatty acid ester, 0.5-1 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2-3 parts of antioxidant, and 6-10 parts of ultraviolet absorber; the outer sheath comprises the following raw materials in parts by weight: 80-100 parts of cross-linked polyethylene, 10-20 parts of nano-barium sulfate, 1-3 parts of plasticizer, 5-10 parts of flame retardant, 0.5-1 parts of antioxidant, 1-2 parts of ultraviolet absorber, and 0.5-1 parts of light stabilizer.
2. The aging-resistant overhead insulated conductor according to claim 1, characterized in that: The insulating layer comprises the following raw materials in parts by weight: 55-65 parts of perfluoroether rubber, 1.5-2.5 parts of mica powder, 0.2-0.4 parts of fatty acid ester, 0.7-0.9 parts of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2.4-2.8 parts of antioxidant, and 7-9 parts of ultraviolet absorber; the outer sheath comprises the following raw materials in parts by weight: 85-95 parts of cross-linked polyethylene, 14-18 parts of nano-barium sulfate, 1.5-2.5 parts of plasticizer, 7-9 parts of flame retardant, 0.7-0.9 parts of antioxidant, 1.4-1.8 parts of ultraviolet absorber, and 0.7-0.9 parts of light stabilizer.
3. The aging-resistant overhead insulated conductor according to claim 1, characterized in that: The weight ratio of the fatty acid ester to the mica powder is 1:(23-27).
4. The aging-resistant overhead insulated conductor according to claim 1, characterized in that: The nano-barium sulfate is prepared by modification, specifically: a titanate coupling agent and liquid paraffin are mixed in a volume ratio of 1: (1-2), dried nano-barium sulfate is added, and the mixture is stirred at 80-120° C. for 30-60 minutes at a stirring rate of 1000-3000 r / min, and finally crushed to 50-200 nm to obtain modified nano-barium sulfate.
5. The aging-resistant overhead insulated conductor according to claim 4, characterized in that: The weight ratio of the titanate coupling agent to the nano-barium sulfate is 1: (100-200).
6. The aging-resistant overhead insulated conductor according to claim 1, characterized in that: The outer sheath further comprises the following raw materials in parts by weight: 5-10 parts of nano zinc oxide and 0.05-0.5 parts of polyethylene wax.
7. The aging-resistant overhead insulated conductor according to claim 6, characterized in that: The weight ratio of the polyethylene wax to the nano zinc oxide is 1:(20-80).
8. A method for preparing the aging-resistant overhead insulated conductor according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing, extruding and vulcanizing the raw materials of the insulating layer to obtain the insulating layer material; mixing, extruding and vulcanizing the raw materials of the outer sheath to obtain the outer sheath material; extruding and coating the insulating layer material on the surface of the conductor, and then extruding and coating the outer sheath on the surface of the insulating layer to obtain the aging-resistant overhead insulated conductor.